PRODUCER AND CONSUMER RESPONSES TO GREEN HOUSING LABELS. (28th August 2014) - Shewmake, Sharon; Viscusi, W. Kip
<x xml:space="preserve">Abstract</x> We find "green" labels increase residential property values by an average of 5%. This premium varies by label stringency and across market segments. Builders respond to the stringency of labels by strategically incorporating green features to achieve higher ratings. This strategy seems reasonable as there is no market premium for green features that lead to scores between label rating cutoff values. These results raise important questions as to how green label policies should be designed in order to foster the supply of green features. Gradations of green attributes are influential, particularly for highly rated homes. The most stringent labels have the greatest role at the high price end of the market. (JEL Q20, Q40, R31)